Ozanimod: A First-in-Class Sphingosine 1-Phosphate Receptor Modulator for the Treatment of Ulcerative Colitis. Issue 5 (May 2022) - Choi, David; Stewart, Alyssa P.; Bhat, Shubha
Objective: To review the pharmacological and clinical profile of ozanimod in the treatment of ulcerative colitis (UC). Data Sources: A PubMed search was conducted from inception to July 2021 using the keywords ozanimod, ulcerative colitis, and sphingosine 1-phosphate receptor modulator . Information was also extracted from published abstracts and the package insert. Study Selection and Data Extraction: Phase 2 and 3 studies and relevant literature on ozanimod pharmacological and clinical profiles were reviewed. Data Synthesis: Ozanimod approval was based on True North, a phase 3 trial evaluating ozanimod's efficacy and safety in the treatment of moderate to severe UC. Compared with placebo, ozanimod led to clinical remission in a significantly higher proportion of patients in both the induction and maintenance phase. Additionally, for secondary end points of clinical response, endoscopic improvement, corticosteroid-free remission, and mucosal healing, ozanimod performed significantly better than placebo. Common adverse events included infections, headaches, hypertension, bradycardia, and liver enzyme elevations. Relevance to Patient Care and Clinical Practice: Ozanimod is the first sphingosine 1-phosphate modulator to be approved for UC and is administered orally. Its efficacy profile is comparable with other UC medications. However, its safety profile is unique, requiring extensive assessments prior to initiation of and during treatment. Thus, it is unclear how ozanimod will be positioned in UC treatment. Conclusion: Ozanimod is another option in the growing arsenal of UC treatment. Although it offers a novel mechanism of action and is administered orally, there are important safety, dosing, and pharmacokinetic factors to consider prior to initiation and use.